Penerapan Metode FIFO (First In, First Out) dalam Pengelolaan Gudang Pelumas PT PLN Nusantara Power Up Tanjung Awar-Awar Kabupaten Tuban - Tsaqib, Muhammad Tamim; Sumiati (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study aims to evaluate the application of FIFO (First In, First Out) method in managing the lubricant warehouse at PT PLN Nusantara Power UP Tanjung Awar-Awar. The FIFO method is used to ensure that the first item received is the first item used, thus minimising the risk of product quality degradation due to long storage. This study was carried out using a quantitative descriptive approach, using Reorder Point (ROP) and Reorder Quantity (ROQ) data to analyse the efficiency of storage space and logistics flow. The results of the study indicate that the FIFO method successfully improves warehouse management efficiency, minimises wastage of space and ensures that lubricant quality is maintained. The study recommends the implementation of a new warehouse layout to optimise more efficient and adaptive logistics operations.